SHAPING CAREER INTENTIONS: THE ROLE OF PERCEPTION, MOTIVATION, AND WORK ENVIRONMENT IN ACCOUNTING STUDENTS’ CHOICE OF PUBLIC ACCOUNTING - Annisya Reva Mardiana; Vinny Stephanie Hidayat (PT. ZILLZELL MEDIA PRIMA, 2026)
The goal of this study is to investigate how professional perception, career motivation, and work environment affect accounting students' interest in becoming public accountants. The study population consists of current students enrolled in the Accounting Study Programme at Maranatha Christian University, selected through purposive sampling according to predetermined criteria. This study included 41 respondents in total. Validity and reliability tests, classical assumption tests, partial hypothesis testing (t-test), and simultaneous hypothesis testing (f-test) were employed for analysis after questionnaires were used to collect data. The results of the study indicate that career motivation, rather than professional perception or the workplace, has a favourable and significant impact on interest in becoming a public accountant. Career interest is simultaneously influenced by the three independent factors, with an Adjusted R2 value of 0.578. This means that 57.8% of the variation in career interest can be explained by the research variables. These findings show that motivation has a significant role in students' decisions to pursue careers as public accountants, even though opinions of the industry and working conditions have not yet had a significant impact. This study provides empirical insights to assist academics and practitioners in creating strategies to increase students' interest in the profession of public accounting.